Pulsed laser irradiation of plasma sprayed alumina-zirconia coatings - Omar, Hala Mohamed (AUC Knowledge Fountain, 2013)
Plasma sprayed alumina and zirconia coatings are widely used coatings for many industrial applications. One of the most important applications is the production of thermal barrier coatings (TBCs). As sprayed alumina-zirconia coatings have relatively high degree of porosity and the properties of these coatings, such as high temperature, corrosion resistance, toughness and abrasion resistance may thereby be reduced. Laser surface treatment is one novel method that has potential for eliminating porosity and producing a homogeneous surface layer. In this research work the effect of excimer laser annealing on the surface of alumina-zirconia coatings was investigated. Alumina-40% zirconia (AZ-40) coatings were sprayed with a water-stabilized plasma spray gun. The coated surface was treated by excimer laser having a wavelength of 248 nm and pulse duration of 24 ns. In the first phase of the work an analytical model was developed in COMSOL Multiphysics 4.2 in order to investigate the effect of the defects on the heat distribution at the surface of samples irradiated by KrF beam. The model revealed that much higher temperatures were localized at areas having defects than at continuous surfaces. A detailed parametric study was carried out to investigate the effects of different laser surface treatment parameters including laser energy density (fluence), pulse repetition rate (PRR), and number of pulses on the microstructure, surface morphology, and mechanical properties of the coatings. The surface structure of the treated coating was examined by field emission scanning electron microscope (FESEM) and X-ray diffraction (XRD). Treating the surface with low laser energy of 200mJ/cm2 etched a very thin layer from the coating, which helped revealing the microstructures initially present but hidden on the surface of as sprayed coatings. High laser energy of 800mJ/cm2 resulted in significant changes in the coat surface morphology where eutectic colonies growing in a pool of zirconia matrix were identified on the surface. The surface of untreated coating was continuously alternating up and down; it had a zigzag nature. After irradiating the surface with high laser fluence of 800mJ/cm2 the zigzag nature of roughness profile of untreated coating disappeared. Also irradiating the surface with high pulse repetition rate exhibited "dome-like" structures on the surface, which were associated with an increase in surface hardness.